PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH DAN ALAT PERAGA UNTUK MENINGKATKANMOTIVASI DAN AKIVITAS BELAJAR SISWA KELAS XI ADMINISTRASI PERKANTORAN PADA POKOK BAHASAN SISTEM KEARSIPAN SMK NEGERI 1 BAWANG BANJARNEGARA - Partono, Partono; Novitarini, Resty (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
It is needed the learning media based on Macromedia Flash and Teaching Aid in the teaching learning process to improve studentsâ motivation and activity. It was a class action research. the subject of the research was XI grade Office Administration Students in SMKN 1 Bawang Banjarnegara. It was a cycle design which consisted of planning, action, observation and reflection. The data were collected by questionnaire and observation sheets. The result of the study showed that the average of students motivation was 64.3% on the 1st cycle and rose to 72.0% on the 2nd cycle and then increased up to 91,2% on the 3rd cycle which was on very high category. Whereas, the studentsâ activities on the 1st cycle was 40% increased up to 70% on the 2nd cycle was, and rose 88% on the 3rd cycle on the very high category. Consequently, the increase ofÂ students motivation and activities gave impact to studentsâ learning result. It was 69.8 with classical completeness was 54,8% on the 1st cycle, then increased up to 72,2 with the classical completeness was 83.9 on the 2nd cycle, and the finally rose to 85.2 with the classical completeness was 93.5% on the 3rd cycle.